Effect of substrate concentration on profile growth of candida tropicalis ifo 0618 - Siti Nur Hatika, Abu Bakar (2014)
This study presents effect of substrate concentration on the profile growth of Candida tropicalis IFO 0618. Different substrate concentration; D-Glucose were introduced to Candida tropicalis IFO 0618 in the Solid State Fermentation (SSF) process. The effect of substrate concentration on the profile growth of Candida tropicalis IFO 0618 was analyzed using UV-Vis Spectrophotometer and High Performance Liquid Chromatography (HPLC). The kinetic parameter (μmax) was also calculated to describe the microbial growth. From the laboratory data, the specific growth rate (μ), maximum specific growth rate (μmax) and half saturation coefficients (KS) were determined using the Monod equation. The maximum observed growth rate (μmax) for Candida tropicalis IFO 0618 was at the substrate concentration of 8.5 (g/g) with μmax value of 1.9991 hr-1, specific growth rate (μ) of 0.0821 hr-1 and half saturation coefficients (KS) of 198.4663 g/l. Result from the High Performance Liquid Chromatography also shows that there was sorbitol produced at 8.5 (g/g) substrate concentrations